Advances in Alternative Measures in Plant Protection - Mechora, Špela; Šunjka, Dragana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Due to increasing concern about the use of pesticides and its potential side effects, this book considers the development and application of alternative, environmental-friendly, plant protection methods for the control of weeds, disease, and pests (predators, parasitoids, competitors, plant-plant interactions, microelements, biopesticides). Some of the main advantages of the measures presented in papers are the absence of toxicity to humans and vertebrates, beneficial organisms, and the environment, as well as the absence of pest resistance. In order to provide sustainable and eco-friendly food production, those are important subjects, both in conventional, organic and integrated agricultural farming. Through reviews and original research articles, this reprint covers all aspects of alternative measures in plant protection.